The Organizational Voice: The Importance of Voice Pitch and Speech Rate in Organizational Crisis Communication. (October 2019) - De Waele, Aurélie; Claeys, An-Sofie; Cauberghe, Verolien
Research on crisis communication has mainly focused on verbal aspects of organizational responses. However, the nonverbal cues of the organizational spokesperson communicating about the crisis may also influence stakeholders' perceptions. This study examines the impact of two vocal cues, voice pitch and speech rate. In addition, the study examines how these cues affect perceptions of organizations depending on the message's verbal content. A 2 (voice pitch: low vs. high) × 2 (speech rate: slow vs. fast) × 2 (crisis response strategy: deny vs. rebuild) between-subjects experimental design was conducted. Results show that voice pitch and speech rate affected postcrisis reputation. However, these vocal cues affected perceptions only when the organization applied a rebuild strategy (i.e., apology) and not in the case of a deny strategy. This interaction between verbal and vocal cues was partly mediated by vocal attractiveness.